The Validation of the development of MIKiR-based Learners' Worksheets on the Theme "Always Saving Energy" among the Fourth Graders of Elementary School - Andi Suhandi; Issaura Sherly Pamela; M. Agus Mubarok; Khairul Amri; Amalia Oktavia (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2021)
This study aims to develop a valid student worksheet based on MIKiR on the theme of always saving energy in grade IV elementary school. The research uses the method of research and development model of the development of Analyze, Design, Develop, Implement, and Evaluate (ADDIE) which will produce student worksheets. This research is the 3rd stage of the development model used, namely: the stages of development. The data in this study are ways to develop valid student worksheets. Data were collected through a validation questionnaire and analyzed with descriptive quantitative. The results obtained show that the students 'worksheets that are developed are in the valid category with a score of 60. The conclusion of this research and development is that through the development procedure of the ADDIE development model, the researcher is able to produce students' worksheets based on thinking on the theme of always saving energy class IV valid primary school.